THE ROLE OF EMPLOYEE WORK MOTIVATION IN OVERCOMING PRODUCTION PROBLEMS AT RCD LEATHER PASURUAN MSMEs - Faiz, Mohammad; Almanshur, Fauzan (JURNAL EKBIS, 2024)
This study aims to determine the role of employee work motivation in overcoming production problems at the Rcd Leather MSMEs in Pasuruan. As an economic actor in the MSMEs sector, Rcd Leather faces various challenges in its production process, including unstable raw material supply and limited workforce skills. This study uses a qualitative approach using interview and observation methods with employees of the Rcd Leather MSMEs . The results of the study indicate that work motivation, both intrinsic and extrinsic, plays an important role in improving employee performance, increasing production efficiency, and overcoming various obstacles in work. A deeper understanding of the driving factors is expected to enable UMKM managers to develop more effective strategies to increase the competitiveness.